Respuesta :

Answer:

The 4 t h term is   f(4)   = 143

Step-by-step explanation:

Explanation:-

Given  function f(1) = -4

Given 'nth' term is  f(n) = -3f(n-1) +5

Put n =2         f(2) = -3 f(2-1) +5

                             = -3 f(1) +5

                             = -3 (-4) +5

                             = 12 +5

                       f(2) = 17

put n= 3      

                         f(n) = -3f(n-1) +5  

                        f(3) = -3 f(3-1) +5

                            = -3f(2) +5

                           = -3(17) +5

                           = -51+5

                      f(3) = -46

Put n=4

                  f(n) = -3f(n-1) +5

                 f(4)  = -3f(4-1) +5

                 f(4)  = -3f(3)+5

                f(4)   = -3(-46)+5

                f(4)   = 138 +5

                f(4)   = 143

Final answer:-

The 4 t h term is   f(4)   = 143